La construction de la forme urbaine de Pontoise au Moyen Âge : entre « impensé » et stratégies des élites - Sandrine Robert (Archéologie Médiévale)
The construction of the town of Pontoise between Antiquity to the sixteenth century is studied through the analysis of its urban form, archaeology and history. Fossilised forms have been found: disappeared castle and church and the limits of the first castrum… The control of inter-regional circulation and new centres, created at the gates of the first castrum, have a great importance in urban form development. Through the change of scale, we can see both the importance of the heritage and of the spontaneous in the construction of urban form. It is the result of social actions without any will or awareness to act on the urban form. But urban form is the result of the action of urban elites too who want to control circulation and market places and act on limited spaces.